Effect of lipids and oleic acid on biomass development in anaerobic fixed-bed reactors. Part I: biofilm growth and activity - Alves, M. M. (2001)
Two similar anaerobic fixed-bed bioreactors which allowed the biomass to be periodically withdrawn were run in parallel. After feeding each digester with synthetic dairy wastes of different lipid content (Period I), both digesters were fed with increasing sodium oleate concentrations with skim milk as co-substrate (Period II) and oleate as the sole carbon source (Period III). In Period I, the digester fed with lipids was more effcient and exhibited lower levels of volatile fatty acids than the digester fed without lipids. The biofilm built up in the presence of lipids was thinner, but more resistant to the presence of oleate than the biofilm formed in the absence of lipids, which lost 53% of its solids after contacting with oleic acid. The specific methanogenic activity with butyrate as substrate was enhanced in the presence of lipids, but no significant effect was detected on the acetoclastic and hydrogenophilic activities, which remained similar for both digesters along the trial period.